2021
DOI: 10.3389/fcvm.2021.805234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the CHA2DS2-VASc Score for the Prediction of Death in Elderly Patients With Coronary Artery Disease and Atrial Fibrillation

Abstract: Purpose: Coronary artery disease (CAD) and atrial fibrillation (AF) often coexist and lead to a much higher risk of mortality in the elderly population. The aim of this study was to investigate whether the CHA2DS2-VASc score could predict the risk of death in elderly patients with CAD and AF.Methods: Hospitalized patients aged ≥65 years with a diagnosis of CAD and AF were recruited consecutively. Patients were divided into 5 groups according to the CHA2DS2-VASc score (≤2, =3, =4, =5, and ≥6). At least a 1-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The CHA2DS2-VASc score is a classical scoring system constructed to assess the thromboembolic risk and guide anticoagulant therapy in patients with atrial fibrillation and considers variables such as age (≥75 years: 2 points; 65–74 years: 1 point), female gender (1 point), heart failure (1 point), hypertension (1 point), diabetes (1 point), stroke (2 points), and vascular disease (1 point), which are easy to calculate [ 8 ]. The use of the CHA2DS2-VASc score has not only been validated in a population with nonvalvular atrial fibrillation but specific parameters have also been reported as independent predictors of stroke and death in the general population as well as in patients with coronary heart disease [ 9 ]. Studies have shown that the CHA2DS2-VASc score accurately predicts adverse events after acute coronary syndrome (ACS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CHA2DS2-VASc score is a classical scoring system constructed to assess the thromboembolic risk and guide anticoagulant therapy in patients with atrial fibrillation and considers variables such as age (≥75 years: 2 points; 65–74 years: 1 point), female gender (1 point), heart failure (1 point), hypertension (1 point), diabetes (1 point), stroke (2 points), and vascular disease (1 point), which are easy to calculate [ 8 ]. The use of the CHA2DS2-VASc score has not only been validated in a population with nonvalvular atrial fibrillation but specific parameters have also been reported as independent predictors of stroke and death in the general population as well as in patients with coronary heart disease [ 9 ]. Studies have shown that the CHA2DS2-VASc score accurately predicts adverse events after acute coronary syndrome (ACS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2 , all simulated events in both arms were within 10% of relative difference when compared with the reported data from the mAFA-II trial. The simulated 5-year survival rate determined by the model (73.5%) was also compared to that reported (68.9%) for the Chinese elderly population with AF (CHA 2 DS 2 -VASc score of 3), and the relative difference was found to be 6.67% [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The model demonstrated accuracy with acceptable differences between simulated and reported rates. The higher 5-year survival rate generated in the present model was likely due to the model population being less elderly and having fewer comorbidities compared to patient characteristics in the cohort study [ 31 ]. For a more precise estimation of the cost-effectiveness over a lifetime scale, a clinical trial investigating the long-term effectiveness of mHealth-based care is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were included in the study if they had both SCAD and nonvalvular AF. SCAD includes stable angina, previous myopathy infarction and ischemic cardiomyopathy [19]. Nonvalvular atrial brillation refers to atrial brillation without mechanical valve prosthesis and rheumatic mitral stenosis [5,20].…”
Section: Patientsmentioning
confidence: 99%